Effect of Salinity Adaptation Technique on Survival and Growth Rate of Patin Catfish, Pangasius sp. - K. Nirmala; D.P. Lesmono; D. Djokosetiyanto (Jurnal Akuakultur Indonesia)
This study was carried out to determine the effect of salinity adaptation techniques on growth and survival of patin catfish Pangasius sp. fry.  Fry of 1.5-2.0 inch in length were reared in the water with different of the initial salinity of 1, 2, 3, 4 and 5 ppt.  Salinity was then daily increased by duplicated the initial water salinity until fish died.  The results of study showed that fry could survive by initial salinity adaptation of 1 ppt and then increasing the salinity by 1 ppt/day to reach 27 ppt.  In the other treatments, all fry died after the salinity reach 18-25 ppt.